Cognitive and Behavioral Deficits in Neurocutaneous Syndromes - J Gordon Millichap (Pediatric Neurology Briefs)
Cognitive and behavioral features of Sturge-Weber syndrome, tuberous sclerosis, and neurofibromatosis are summarized by a literature review (113 references) at the New York University, New York.